Perancangan Sistem Pendukung Pengambilan Keputusan Pemilihan Ekstrakurikuler Dengan Metode AHP (Analytical Hierarchy Process) Dan SMART (Simple Multi Attribute Rating Technique) Di SMKS Binong Permai An-Nurmaniyah - Dede Imam Saputro; Entis Sutrisna (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Information technology is growing rapidly at this time, making the need for information and data processing very important in many aspects of life. The rapid development of technology has an impact on an organization or agency, in this case schools that need a data processing system that can help quickly and accurately. Web-based information systems can be used as a means of increasing information. Technology can help simplify a job such as faster data processing, decisions that can be taken more quickly and accurately and save costs and time. The number of extracurricular activities found at SMKS Binong Permai makes it difficult for students to choose extracurricular activities that match their interests and talents. A decision-making system or decision support system is a computer-based information system that can produce a variety of useful decision options to help management deal with structured and unstructured problems using data and models. With this decision-making support system, it is hoped that students will be able to map students to extracurricular activities according to their interests and talents. So students can develop and excel in extracurricular activities that are in accordance with their interests and talents. And it is also expected to be able to help overcome the problems faced by school management in registering students who take extracurricular activities.